(untitled) (Boletín Semillero de Investigación en Familia, 2024)
Introduction: The Human Immunodeficiency Virus is a disease of great concern and attention worldwide due to its impact on public health. It affects the immune system, weakening it and leaving the body vulnerable to various infections and diseases. In particular, adolescents are in a crucial stage of development, where the acquisition of knowledge about HIV and preventive measures is essential for their well-being and that of the community Objective: Determine the level of knowledge of preventive measures for the Immunodeficiency Virus Human in adolescents from Eighth to Tenth grade of an educational institution in Barranquilla 2022-2023 Materials and methods: descriptive, cross-sectional study. The population was 103 students with a sample of 56 students, and convenience sampling. The instrument used was based on a previous study carried out in Peru on the knowledge and practice of HIV/AIDS preventive measures in adolescents. Results: 51.7% of the students were female, 48.2% male, 42.8% % were 14 years old, 26.7% were 13 years old, 37.5% were in ninth grade, 32.1% were in eighth grade, and 30.3% were in tenth grade. When determining the level of knowledge of the students, ADEQUATE KNOWLEDGE and a minority of INADEQUATE KNOWLEDGE were evident. Conclusion: The findings indicated that the adolescents surveyed have a high level of knowledge about certain aspects of HIV/AIDS. This suggests that educational authorities, Parents and/or guardians should work on plans to improve strategies to prevent HIV infection.